The four principles of great design learn by video - Williams, Robin (Peachpit Press, 2014)
"Robin Williams, author of The Non-Designer's Design Book, is beloved and respected worldwide for her frank, funny, down-to-earth method for teaching design fundamentals. In The Four Principles of Great Design Learn by Video, Robin brings those teachings to video for the first time. In this three-hour course, you'll learn how to effectively use contrast, repetition, alignment, and proximity (C.R.A.P.) to create professional-looking brochures, ads, business cards, and more. Robin explains these core design concepts in the context of real-world design projects that anyone from non-designers to budding professionals can use to gain a solid understanding of what makes great graphic design."--Resource description page.
Title from resource description page (viewed December 12, 2014)
Keywords: Design; Brochures -- Design; Electronic videos